REVIEW OF EMERGING TRENDS IN LOW POWER MULTIPLER - Sheetal Nagar, Seema Nayak,Govind Singh Patel (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
A significant amount of power is consumed by multipliers which in turn results in lowers processing speeds. In this paper we review and investigate the use of low power multiplier to resolve the issues of various applications such as Artificial Intelligence, Machine learning , IOT(Internet of thing), FIR, IIR, DSP and Image processing, multimedia/signal Processing, patter recognition or Image Shrinking and data mining and analysis. Various Schemes and different architectures of low power Multiplier are Analyzed or Compared for betterment of the parameters like Area, Speed, Energy, Power and Delay. Various Tools used for the simulations like Mat lab, Xilinx and Verilog.